REVIEWING THE INFLUENCE OF MENTAL HEALTH AND COPING STRATEGIES ON ACADEMIC PERFORMANCE - Noraida Saidi; Nik Zam Nik Wan; Syuhaila Razak; Suzana San; Azilawati Abdullah@ Abd Aziz; Siti Nor Adawiah Hussin; Normaizatul Akma Saidi (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study investigates the impact of mental health on academic performance among university students in Malaysia through a systematic literature review. By synthesizing findings from various peer-reviewed studies, the research identifies key themes, including the significant negative correlation between mental health issues (such as depression, anxiety, and stress) and academic performance. Additionally, it highlights the influence of broader societal issues, gender disparities, and the importance of socioemotional skills and well-being in academic success. The methodology involves a comprehensive search of electronic databases, stringent inclusion and exclusion criteria, and robust meta-analytic procedures to ensure unbiased and reliable analysis. The findings underscore the critical need for holistic approaches and effective mental health interventions to support students’ academic success and overall well-being. This study provides valuable insights and recommendations for university administrators, policymakers, and mental health professionals, aiming to enhance support systems for Malaysian university students. Future research directions include exploring cultural differences, longitudinal effects, and the efficacy of various interventions for coping strategies.